Alternative calculation on transient elasto-hydrodynamic lubrication. Issue 2 (12th March 2018) - Zhu, Shaocheng; Zhang, Weihua; Nelias, Daniel
Abstract : Purpose: The purpose of this study is to propose a new method to solve transient elasto-hydrodynamic lubrication (EHL) problem. Design/methodology/approach: First, the steady-state EHL solution is modified so that the elastic deformation theory is combined with oil film stiffness distribution instead of steady-state Reynolds equation. Second, subsequent dynamic EHL procedure develops, recursively using transient distributed oil film stiffness and damping, where each time-marching solution is iteratively searched by ensuring both oil film force growth and elastic deformation update for each load increment. Findings: This method increases calculation speed and provides both distributed EHL stiffness and damping for transient regimes. Originality/value: This method is of interest for fast applications such as rolling bearings or gears.